Increased Mitochondrial Pro-oxidant Activity Mediates Up-regulation of Complex I S-glutathionylation via Protein Thiyl Radical in the Murine Heart of eNOS(−/−) - Kang, Patrick T. (Free Radic Biol Med, 2014)
In response to oxidative stress, mitochondrial Complex I is reversibly S-glutathionylated. We hypothesized that protein S-glutathionylation (PrSSG) of Complex I is mediated by a kinetic mechanism involving reactive protein thiyl radical (PrS(•)) and GSH in vivo. Previous studies have shown that in vitro S-glutathionylation of isolated Complex I at the 51 kDa and 75 kDa subunits was detected under the conditions of (•)O(2)(−) production, and mass spectrometry confirmed that formation of Complex I PrS(•) mediates PrSSG. Exposure of myocytes to menadione resulted in enhanced Complex I PrSSG and PrS(•) (Kang et al Free Radical Biol. Med. 2012; 52: 962–73). In this investigation, we tested our hypothesis in the murine heart of eNOS(−/−). The eNOS(−/−) mouse is known to be hypertensive and develops the pathological phenotype of progressive cardiac hypertrophy. The mitochondria isolated from the eNOS(−/−) myocardium exhibited a marked dysfunction with impaired state 3 respiration, a declining respiratory control index, and decreasing enzymatic activities of ETC components. Further biochemical analysis and EPR measurement indicated defective aconitase activity, a marked increase in (•)O(2)(−) generation activity, and a more oxidized physiological setting. These results suggest increasing prooxidant activity and subsequent oxidative stress in the mitochondria of the eNOS(−/−) murine heart. When Complex I from the mitochondria of the eNOS(−/−) murine heart was analyzed by immuno-spin trapping and probed with anti-GSH antibody, both PrS(•) and PrSSG of Complex I were significantly enhanced. Overexpression of SOD2 in the murine heart dramatically diminished the detected PrS(•), supporting the conclusion that mediation of Complex I PrSSG by oxidative stress-induced PrS(•) is a unique pathway for the redox regulation of mitochondrial function in vivo.